Marketing Management of Islamic Educational Institutions: Manajemen Pemasaran Lembaga Pendidikan Islam - Ilahi, Farid Kurnia; Taufiqurrahman, Taufiqurrahman (Universitas Muhammadiyah Sidoarjo, 2023)
Good marketing management is one of the factors to attract new prospective students. The purpose of this study is to describe the marketing management of educational institutions and to describe the factors that hinder and support the implementation of marketing in SMP Al Islamiyah Putat. This research is a qualitative research with research subjects including the principal, coordinator or person in charge of the school, teachers, and the community environment of SMP Al-Islamiyah Putat. From the research conducted, it was found that (1) Marketing planning is based on the school's vision and mission with modifications according to field conditions, (2) Organization has been running as expected under the leadership of the Principal who collaborates with stakeholders, (3) The movement process is based on the vision and mission which is strengthened by